PENGARUH KETERAMPILAN SELF ADVOCACY TERHADAP PELAJARAN MATEMATIKA SISWA SMP - nur annisa rosyiidah; ANGGITA MAHARANI (JEDMA Jurnal Edukasi Matematika, 2023)
This study aims to determine the effect of self-advocacy skills on junior high school mathematics. The method used is a quantitative method with a student response questionnaire as an instrument. The results showed that self-advocacy skills in students' mathematics lessons can be seen from the results of the questionnaire percentage, namely students' Self Awareness Skills by 25%, Student Communication Skills by 26%, Problem Solving and Decision Making Skills for students by 25%, Students' Responsibility Awareness Skills by 23%.